PENGARUH PERKAWINAN DI BAWAH UMUR TERHADAP TINGKAT PERCERAIAN DI PENGADILAN AGAMA SURAKARTA TAHUN 2023 - Afifatimah, A; Wibowo, Muhammad Kurniawan Budi; Baehaqi, B (AL HUKMU: Journal of Islamic Law and Economics, 2023)
This research is motivated by the increasing number of divorces in the city of Surakarta and the increasing number of applications for marriage dispensations. Because of that, research was carried out whether there was a correlation between the two. This study aims to determine the effect of the practice of underage marriages on the divorce rate in the Surakarta Religious Court and to find out what are the factors that influence underage marriages to divorce in the city of Surakarta in 2023. This study uses a quantitative approach, with observation techniques at the Surakarta Religious Court, distributing questionnaires to perpetrators of underage marriages, and documentation. The data collection technique used in this study was a descriptive analysis technique that was processed using the SPSS 22 program. The results showed that the correlation value / level of relationship between variables (R) was 0.713 and a coefficient of determination (R Square) was 0.508 which means that there is an influence of the independent variable (underage marriage) on the dependent variable (divorce rate). Based on the results of testing the underage marriage hypothesis, the value of Sig. (0.000) < 0.05, then H0 is rejected and H1 is accepted, namely variable X (underage marriage) affects variable Y (divorce rate). that the factors influencing underage marriage actors in Surakarta to file for divorce in 2023 are economic, psychological, moral crisis, parental involvement in making decisions, domestic violence, selfishness, and third person